Sosialisasi Mengenai Gut Microbiota dan Probiotik Serta Perannya Bagi Kesehatan Saluran Cerna Pada Anak Gizi Kurang - Husnita Komalasari; Destiana Adinda Putri; Lalu Danu Prima Arzani; Muhammad Nizhar Naufali; Nurul Hidayah; Rina Heldiyanti (LPPM Universitas Bumigora, 2023)
The purpose of this community service activity is to provide knowledge to the community about the gut microbiota and probiotics and their role in gastrointestinal health, especially in children with undernutrition. Children with malnutrition experience changes in the composition of the gut microbiota so that they are more susceptible to gastrointestinal infections. The gut microbiota can be positively or negatively related to influencing nutrient absorption in the gut. Probiotics are live bacteria that are able to provide health effects such as maintaining the balance of the intestinal microbiota and increasing the body's immunity. In this community service, there will be outreach activities regarding the gut microbiota and the importance of consuming probiotics as an effort to prevent dysbiosis at SDN 3 Belanting, East Lombok. This activity was carried out by Community Service Program (PKM) of Bumigora University. The implementation of this community service activity has been able to increase the knowledge of students and parents of targeted students of socialization regarding nutrition, nutritional status, gut microbiota, the importance of gastrointestinal health, especially its relation to nutritional status and the role of probiotics on digestive health.